Uniqueness of meromorphic functions sharing one value or fixed points - Xiao-Bin Zhang (Հայաստանի ԳԱԱ)
In this paper we study the uniqueness of meromorphic functions sharing a nonzero finite value or fixed points.
Keywords: Mathematics; Science